2019
DOI: 10.1039/c9ra04947a
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical non-woven fabric NiO/TiO2 film as an efficient anode material for lithium-ion batteries

Abstract: Hierarchical non-woven fabric NiO/TiO 2 film is prepared using a facile two-step synthesis by electrospinning and subsequent hydrothermal reaction to yield TiO 2 film decorated with NiO nanosheets. As an anode material for Li-ion batteries, the NiO/TiO 2 composite exhibits discharge and charge capacities of 1251.3 and 1284.3 mA h g À1 , with good cycling performance and rate capability.Characterization shows that the NiO nanosheets are distributed on the surface of the TiO 2 nanofibers.The total specific capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The hkl plane values revealed that NiO NPs have a face-centered-cubic (FCC) structure (JCPDS file no. 65-2901). , A well-defined sharp peak indicates the higher crystallinity of the synthesized NiO NPs. Hence, crystallite sizes of NPs were estimated using the Debye–Scherrer formula.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hkl plane values revealed that NiO NPs have a face-centered-cubic (FCC) structure (JCPDS file no. 65-2901). , A well-defined sharp peak indicates the higher crystallinity of the synthesized NiO NPs. Hence, crystallite sizes of NPs were estimated using the Debye–Scherrer formula.…”
Section: Resultsmentioning
confidence: 99%
“…65-2901). 57 , 58 A well-defined sharp peak indicates the higher crystallinity of the synthesized NiO NPs. Hence, crystallite sizes of NPs were estimated using the Debye–Scherrer formula.…”
Section: Resultsmentioning
confidence: 99%
“…For Co 3 O 4 @ NC/NiO, three small diffraction peaks are observed at 37.9° (111), 43.2° (200), and 63.6° (220), confirming the formation of NiO from Ni(OH) 2 as per JCPDS No. 65-2901 because the heat treatment led to the removal of H 2 O molecules and decomposition of Ni(OH) 2 [56,57] (Figure 3b). The heat treatment at 700 °C resulted in the Co-MOF-templated formation of Co 3 O 4 nanoparticles embedded with N-doped carbon on NiO; the diffraction peaks at 31.1° (220), 35.6° (311), and 66.3° (440) coincide with the XRD pattern of JCPDS Card no.…”
Section: Resultsmentioning
confidence: 99%
“…As is well known, owing to the low initial Coulombic efficiency and capacity of carbon materials, exploring carbon-free electrode materials has been deemed as a hotspot worth studying. Therefore, significant progress has been made in the system of NiO@metallic oxide, including Fe 2 O 3 54 , TiO 2 , , Co 3 O 4 , MnCo 2 O 4 59 , NiCo 2 O 4 , , NiFe 2 O 4 62 , and ZnCo 2 O 4 63 . TiO 2 , as a “zero-strain” material, acted as a template for the growth of NiO, resulting in the regular distribution of NiO. , As shown in Figure f, Zhang et al reported that hierarchical nonwoven fabric NiO/TiO 2 films act as an anode material for lithium-ion batteries.…”
Section: Niomentioning
confidence: 99%